Aktivitas Amilolitik Bakteri Sedimen Mangrove Pantai Logending, Ayah, Kebumen pada Suhu dan pH Berbeda - Rahmawati, Alfiani; ., Oedjijono; Ryandini, Dini (Fakultas Biologi Universitas Jenderal Soedirman, 2021)
Mangrove sediment is a source of various microorganisms that degrade leaf litter or parts of mangrove plants, including amylolytic bacteria. Bacteria isolated from the mangrove sediments of the Logending beach have not yet known their amylolytic ability. Optimum amylase activity can be influenced by temperature and pH. This study aims to determine the ability of mangrove sediment bacterial isolates to produce amylase enzymes, to determine the pH and temperature for optimum amylase activity, and to identify amylase-producing bacteria. The research was conducted by survey method. The research stages included screening for amylolytic bacteria, preparation of growth curves, amylase production, optimizing amylolytic activity at various temperatures (35ºC; 36ºC; 37ºC; 38ºC) and pHs (4.5; 5; 5.5; 6) and characterization of amylolytic isolates. The parameters measured were amylolytic index, amylase activity quantitatively, total number of bacteria, and identity of amylolytic bacteria from mangrove sediments. Data analysis was done descriptively. The results showed that the highest amylolytic index were shown by isolate LG113 with an amylolytic index value of 9.86 from 10 amylolytic isolates from mangrove sediments. The optimum temperature for amylase activity was 37ºC, which was 2.13 U/mL and the optimum pH was 6, which was 2.14 U/mL. The total number of amylolytic bacterial cells at the end of the production period was 1.94.1013 cfu/mL. The amylolytic isolate LG113 belongs to Bacillus genera.